Studi meta analisis: Emotion regulation training untuk menurunkan tingkat kecemasan - Lestari, Devi Damar; Yudiarso, Ananta (Jurnal Psikologi Udayana, 2022)
This research aims to determine the effectiveness of emotion regulation training to reduce anxiety levels. The method used in this study is a meta-analysis by reviewing the previous literature of 14 journals published internationally. The number of participants in this study were 877 subjects consisting of 469 subjects in the experimental group and 408 subjects in the control group. Then processing the M, SD, N data in each group to find the effect size value. The result of the effect size of the random effect model is -0.295 (95% CI = -1.69 to 1.10), I 2 (inconsistency) = 98.72%, and Egger value: bias = 0.212. Based on these data, training based on emotion regulation is not effective enough in reducing anxiety levels (small effect size).